Capturing physiological hemodynamic flow and mechanosensitive cell signaling in vessel-on-a-chip platforms - Martier, A.; Chen, Z.; Schaps, H.; Mondrinos, M. J.; Fang, J. S. (Frontiers in Physiology, 2024)
Recent advances in organ chip (or, "organ-on-a-chip") technologies and microphysiological systems (MPS) have enabled in vitro investigation of endothelial cell function in biomimetic three-dimensional environments under controlled fluid flow conditions. Many current organ chip models include a vascular compartment; however, the design and implementation of these vessel-on-a-chip components varies, with consequently varied impact on their ability to capture and reproduce hemodynamic flow and associated mechanosensitive signaling that regulates key characteristics of healthy, intact vasculature. In this review, we introduce organ chip and vessel-on-a-chip technology in the context of existing in vitro and in vivo vascular models, then briefly discuss the importance of mechanosensitive signaling for vascular development and function, with focus on the major mechanosensitive signaling pathways involved. Next, we summarize recent advances in MPS and organ chips with an integrated vascular component, with an emphasis on comparing both the biomimicry and adaptability of the diverse approaches used for supporting and integrating intravascular flow. We review current data showing how intravascular flow and fluid shear stress impacts vessel development and function in MPS platforms and relate this to existing work in cell culture and animal models. Lastly, we highlight new insights obtained from MPS and organ chip models of mechanosensitive signaling in endothelial cells, and how this contributes to a deeper understanding of vessel growth and function in vivo. We expect this review will be of broad interest to vascular biologists, physiologists, and cardiovascular physicians as an introduction to organ chip platforms that can serve as viable model systems for investigating mechanosensitive signaling and other aspects of vascular physiology.